DAUR ULANG SAMPAH NON ORGANIK UNTUK INDUSTRI KREATIF RUMAHAN MASYARAKAT DESA SANROBONE - Muhammad Reza Ramdani; nurfadila nurfadila; subhan subhan; Musliha Shaleh (Universitas Indraprasta PGRI, 2021)
The decomposition of non-organic wasted is very difficult and require time tended to be longer as well as the numbered of non-organic wasted that is scattered and accumulated in the village area and as well lacked of knowledge sanrobone villagers about treatment of non-organic wasted, tend to villagers hoarded or burned the waste. The purpose of this dedication to provided knowledge in utilizing and processing of non-organic wasted into household industry products, are ready to be marketed and the new economic pointed of the village. The implementation method is through a non-organic waste recycling training program and provides solutions marketing the results of the management of non-organic wasted. The results achieved in this dedication of village communities able to cultivate non-organic waste into a home craft and communities are able to market physically and through online applications. This kind of devotion still needs to be done again for various processed products so that it can increase the quantity of product types.